UPAYA PENGHEMATAN KONSUMSI ENERGI LISTRIK DI PT. KAWASAN INDUSTRI MAKASSAR MELALUI WALK-THROUGH AUDIT METHOD - Alfarizy, Muhammad Mahdiy; Wibawa, Unggul; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
Energy security plays an important role in supporting national development. To maintain energy security, energy conservation is carried out by reducing energy use in producing goods or services. To analyze energy use is conduct an energy audit. This research aims to obtain the Energy Use Intensity (EUI), electrical energy utilization patterns, and energy saving opportunities in the Head Office and Waste Water Treatment Plant (WWTP) PT. Kawasan. Industri Makassar (PT. KIMA), using WalkThrough Audit method. The calculation of the EUI refers to the building area and electrical energy consumption in 2022-2023. The electrical energy utilization pattern focuses on the daily load of electrical energy consumption, such as measuring the level of light illuminance (lux), calculating the electric power of lamps, calculating the Energy Efficiency Ratio (EER) for the Air Conditioner (AC), and calculate the appropriate AC capacity for each room. The results of the EUI value calculation show that the criteria are very efficient in the Head Office in 2022-2023 and very efficient in the WWTP office in 2022, which decreases to efficient in 2023. The lux level in 76.47% of the rooms in the Head Office and 70% of the rooms in the WWTP Office is below the SNI 6197:2020 standard. The type of AC installed is energy efficient, but the AC capacity is too big in that 35% of the rooms in the Head Office and 57% of the rooms in the WWTP Office. The results of the IKE analysis show a small influence on energy saving opportunities. Meanwhile, the analysis of electrical energy utilization patterns shows a large influence on providing energy saving opportunities. Keyword : Energy Audit, Energy Use Intensity (EUI), Energy Efficiency Ratio (EER)